Using Peer-Modo Feedback at the Pre-Writing Stage to Improve Year 4 Pupils’ Writing Performance - Yuk, Aderlin Chung Kim; Yunus, Melor Md (Journal of Education and e-Learning Research, 2020)
The main problem faced by English teachers in the current English as a Second Language (ESL) writing classroom was a lack of strategies to support the process of teaching and learning writing that would help to enhance the content quality of pupils’ writing performance. Additionally, primary pupils were found to face difficulties with getting started in writing. Peer feedback is an important tool for encouraging and consolidating learning. A quasi-experimental research study was implemented to investigate the effectiveness of an online peer-feedback strategy using Edmodo at the pre-writing stage to improve pupils’ writing performance. A writing pre-test and post-test were administered to 36 Primary 4 respondents from a Chinese-vernacular school in a state in southern Malaysia to reveal their writing test scores before and after the intervention. Documents such as pre-test and post-test writing excerpts and Peer-Modo feedback comments were analyzed to corroborate the quantitative findings of the test scores. The results of the mean scores of the pre-test and post-test showed that there was significant improvement in pupils’ writing ability. The document analysis reflected significant improvements in terms of the content quality of their writing after conducting Peer-Modo feedback. Consequently, online peer feedback strategies should be taken into consideration in the teaching of writing in the ESL classroom.